Konsep Ekonomi Kebijakan dalam Pemerintahan Presiden Joko Widodo - Elza Rahmawati; Eli Apud Saepudin; Dina Dwi Apriani; Aulia Fitriani; Lia Rosiana (Pt. Anagata Sembagi Education, 2024)
This research is a literature review of the Economic Policy Package launched by President Joko Widodo in 2015. The Economic Policy Package consists of several volumes. When it was first launched, namely Volume 1, the economic policy package aimed to stimulate the real sector and drive the economy. Volume 1 of the Economic Policy Package is one of 16 economic policy packages launched until 2018. A review of the literature related to the Economic Policy Package volume 1 was conducted to identify the latest research related to economic policy packages and provide an assessment of the effectiveness of the Government's policies related to the Economic Policy Package. There are several aspects of national economic development, such as economic growth, inflation, and fiscal and monetary policies.Literature both in the form of academic studies and opinions and public perceptions of economic policy packages are explored in depth mainly by using search engines in the form of both formal and informal studies such as mass media. This study found that the literature related to Economic Policy Package Volume I is relatively limited and the discussion tends to focus on the impact of policies on capital market reactions. In addition, research on economic policy packages is dominated by quantitative approaches. In the future, it is necessary to expand the discussion of economic policy packages with broader theories, use a qualitative approach and dig deeper into the effectiveness of the economic policy packages